Aryan Phillips

2022-02-03

What is the standard form of y=2(x-3)(x-2)(3x-5)?

ribejat1f3

Beginner2022-02-04Added 8 answers

Explanation:

In general the standard form of a polynomial is

$y={a}_{n}{x}^{n}+{a}_{n-1}{x}^{n-1}+\dots +{a}_{2}{x}^{2}+{a}_{1}{x}^{1}+{a}_{0}$

To achieve the standard form, multiply out the expression

$y=2(x-3)(3{x}^{2}-6x-5x+10)$

$y=2(3{x}^{3}-11{x}^{2}+10x-9{x}^{2}+33x-30)$

$y=2(3{x}^{3}-20{x}^{2}+43x-30)$

$y=6{x}^{3}-40{x}^{3}+86x-60$

Answer:

$y=6{x}^{3}-40{x}^{3}+86x-60$

In general the standard form of a polynomial is

To achieve the standard form, multiply out the expression

Answer: